“Language means freedom to me” perspectives of Deaf and hard-of-hearing students on their experiences in the English as a foreign language classroom - Urbann, Katharina; Gross, Kristin; Gervers, Alina; Kellner, Melanie (Frontiers in Education, 2024)
The aim of the study is to examine the perspectives of Deaf and hard-of-hearing (DHH) students regarding their experiences in the English as a foreign language (EFL) classroom. Utilizing a qualitative design, semi-structured interviews were conducted with 17 former DHH students who learned English at German schools for the DHH. The findings reveal various language combinations within the EFL classroom, which entirely depend on the teacher. Several critical aspects of the EFL classes were highlighted, including the insufficient foreign sign language competencies of teachers, the juxtaposition of German Sign Language (DGS) signs and spoken English, and the lack of Deaf cultural content and awareness in the teaching. Additionally, the absence of interactive engagement in the EFL classroom was noted as a significant issue. Based on the DHH students' EFL learning experiences, the study also underscores the crucial importance of English and American Sign Language (ASL) as foreign languages for young DHH individuals, particularly for international interactions and social media use.